활선작업 근로자의 건강행태, 일과 관련된 건강문제와 사고에 대한 현황조사 - 김민지; 최은숙 (한국직업건강간호학회지, 2021)
Purpose: The purpose of this study is to identify health behaviors, work-related health problems, and accidents of live-line workers. Methods: The questionnaires were administered to 150 live-line workers in 150 workplaces. A total of 150 questionnaires were collected and 130 were used. Data were analyzed for frequency and percentage by SAS Version 9.3. Results: In terms of eating habits, 62.3% were in the regular-group. Smoking status was 61.5% of smokers and drinking status was 87.7% in the drinking-group. Body mass index was 42.9% for obesity. Most of the workers had problems with sleep. Among the work-related health problems were 98.2% for “upper limb muscle pain”, 92.7% for “back pain”, and 97.2% for “body fatigue”. Among the work-related accidents were 91.7% for “cutting”, 88.4% for “excessive movement”, and 88.3% for “falling”. Conclusion: Safety technology development and effective and efficient work equipment must be used to improve the safety and health of live-line workers. In addition, it is necessary to thoroughly supervise and provide active support for the risk factors and health management to the working environment of live-line workers.